Evasion of NK cell immune surveillance via the vimentin-mediated cytoskeleton remodeling - Peng, Jei-Ming; Chiu, Ching-Feng; Cheng, Jai-Hong; Liu, Hui-Ying; Chang, Yin-Lun; Luo, Jia-Wun; Weng, Yu-Ting; Luo, Hao-Lun (Frontiers in Immunology, 2022)
Cancer immunotherapy uses the immune system to achieve therapeutic effects; however, its effect is still limited. Therefore, in addition to immune checkpoint-based treatment, the development of other strategies that can inhibit cancer cells from resisting immune cytotoxicity is important. There are currently few studies on the mechanism of tumors using cytoskeletal proteins reorganization to participate in immune escape. In this study, we identified cancer cell lines that were sensitive or resistant to natural killer cells in urothelial and lung cancer using the natural killer cell sensitivity assay. We found that immunoresistant cancer cells avoid natural killer cell-mediated cytotoxicity by upregulation of vimentin and remodeling of actin cytoskeleton. Immunofluorescence staining showed that immune cells promoted the formation of actin filaments at the immune synapse, which was not found in immunosensitive cancer cells. Pretreatment of the actin polymerization inhibitors latrunculin B increased the cytotoxicity of natural killer cells, suggesting that cytoskeleton remodeling plays a role in resisting immune cell attack. In addition, silencing of vimentin with shRNA potentiated the cytotoxicity of natural killer cells. Interestingly, the upregulation and extension of vimentin was found in tumor islands of upper tract urothelial carcinoma infiltrated by natural killer cells. Conversely, tumors without natural killer cell invasion showed less vimentin signal. The expression level of vimentin was highly correlated with natural killer cell infiltration. In summary, we found that when immune cells attack cancer cells, the cancer cells resist immune cytotoxicity through upregulated vimentin and actin reorganization. In addition, this immune resistance mechanism was also found in patient tumors, indicating the possibility that they can be applied to evaluate the immune response in clinical diagnosis.